Materials, preparation, performances and mechanism of polyurethane modified asphalt and its mixture: A systematic review - Chaohui Wang; Shuai Huang; Qian Chen; Xiaoping Ji; Kaixi Duan (Journal of Road Engineering, 2023)
With the rapid development of asphalt pavement technology, it has attracted considerable attention to improving the durability of asphalt pavement. An effective action is to use modified asphalt with high performance and durability. Polyurethane (PU) has been used in asphalt pavement engineering to enhance the durability and service life of asphalt pavement because of its excellent high-temperature performance, toughness, wear resistance, aging resistance and oil resistance. However, PU modified asphalt technology is still in the exploratory stage. The preparation, modification mechanism and working performances of PU modified asphalt need to be further clarified. Therefore, this paper summarized the research progress of PU modified asphalt and its mixture. The composition of PU modified asphalt was introduced. The addition methods of PU materials and preparation process parameters of the PU modified asphalt were determined. The modification mechanism of PU on asphalt was discussed. The effects of polyurethane on asphalt were analyzed and the road performances of its mixture were evaluated. Finally, the development tendency towards PU modified asphalt and its mixture were forecasted.